159 Enhanced supportive care (esc): results from the national cquin data (year 1). Issue Volume 8: Issue (2018)Supplement 1 (1st March 2018) - Berman, Richard; Mola, Lisa La; Elliott, Elizabeth; Hall, Nathan; Lockhart, Jill
Abstract : Background: The landscape of cancer care is changing rapidly. As more patients live longer with 'chronic cancer' and new treatments become increasingly available, there is a growing need for oncologists, palliative care specialists and acute physicians to contribute more to the development of expertise in managing problems associated with long-term cancer and cancer survival. ESC is a national cancer centre initiative which aims to implement early involvement of supportive care within oncology. The ultimate aim of ESC is to make available supportive care expertise for patients at any stage, including those with curable cancers. Methods: ESC is being delivered through a national cquin. This has encouraged additional investment allowing resource expansion required to deliver ESC. In most centres, development of ESC has been led by palliative care clinicians and incorporated within palliative care teams. In other centres, this is led by oncologists. Some 'rebranded' the name of their palliative care team to include 'supportive care' or 'symptom control'; whilst others have developed separate 'ESC teams' within their centre. In this 1st phase of ESC, referrals to supportive care are encouraged for patients who are within 6 weeks of a diagnosis of incurable cancer. Results: ESC is a 3-year national project (2016–2019). 23 cancer centres across England signed up to the initiative in 2016–2017. Most of these sites now demonstrate earlier integration of supportive care within cancer through implementation of ESC – some have shown very significant increases in early referrals. In some sites, data points to an impact on reducing emergency admissions. Conclusions: NHS England (NHSE) continues to build the case that ESC delivers improved value – reduced healthcare costs, improved QoL and optimises treatment decision making. Data collection is ongoing nationally and will inform national cancer policy and NHSE strategy. Formal research evaluation of ESC is expected begin in early 2018.